Neuronal cell adhesion molecule regulating neural systems underlying addiction - Hiroki Ishiguro; Kunio Miyake; Koichi Tabata; Chiaki Mochizuki; Takeshi Sakurai; Emmanuel S. Onaivi (Wiley, 2019)
Abstract Aims The human NRCAM gene is associated with polysubstance use. Nrcam knockout mice do not acquire a preference for addictive substances. We aimed to elucidate the role of Nrcam in specific neural circuits underlying congenital preference for substances and the acquisition of addiction. Methods We analyzed gene expression patterns of neural molecules to find a common addiction pathway dependent on Nrcam function. We examined monoaminergic, glutamatergic, and GABAergic systems in the brains of Nrcam knockout mice following treatment with methamphetamine (METH) or saline (SAL) using micro‐array gene expression analysis, which was replicated using TaqMan gene expression analysis. To find a common addiction pathway, we examined similarities and differences between the expression patterns of molecules in METH‐treated mice and in Nrcam knockout mice treated with cocaine (COC). Results Glutaminase expression in brain was reduced in Nrcam heterozygous mice after METH and COC treatment, consistent with our previous study. Metabotropic glutamate receptor 2 expression was reduced in Nrcam heterozygous mice that received either METH or COC treatment. Several other molecules could act in independent addiction pathways involving METH or COC. We also found that GABA receptor subunit g2 expression was reduced in Nrcam heterozygous mice that underwent SAL treatment, and that METH treatment attenuated this reduction. Conclusion Nrcam differentially regulates glutamatergic and GABAergic molecules in naive brains and in brains of animals with acquired addiction. Elucidating the complex neural mechanisms underlying polysubstance use will uncover biological features of addiction and may contribute to the development of effective pharmaceutical treatments.